Improving performance of spatio-temporal machine learning models using forward feature selection and target-oriented validation. (March 2018) - Meyer, Hanna; Reudenbach, Christoph; Hengl, Tomislav; Katurji, Marwan; Nauss, Thomas
Abstract: Importance of target-oriented validation strategies for spatio-temporal prediction models is illustrated using two case studies: (1) modelling of air temperature ( T a i r ) in Antarctica, and (2) modelling of volumetric water content (VW) for the R.J. Cook Agronomy Farm, USA. Performance of a random k -fold cross-validation (CV) was compared to three target-oriented strategies: Leave-Location-Out (LLO), Leave-Time-Out (LTO), and Leave-Location-and-Time-Out (LLTO) CV. Results indicate that considerable differences between random k -fold ( R 2  = 0.9 for T a i r and 0.92 for VW) and target-oriented CV (LLO R 2  = 0.24 for T a i r and 0.49 for VW) exist, highlighting the need for target-oriented validation to avoid an overoptimistic view on models. Differences between random k -fold and target-oriented CV indicate spatial over-fitting caused by misleading variables. To decrease over-fitting, a forward feature selection in conjunction with target-oriented CV is proposed. It decreased over-fitting and simultaneously improved target-oriented performances (LLO CV R 2  = 0.47 for T a i r and 0.55 for VW). Highlights: Random k-fold cross validation (CV) leads to an overoptimistic view on model results. Target-oriented CV is required for reliable error estimates of space-time models. Temporally static variables can lead to spatial over-fitting. Feature Selection in conjunction with target-oriented CV can reduce over-fitting. The proposed modelling framework should become common practice.